2012
DOI: 10.4028/www.scientific.net/kem.504-506.295
|View full text |Cite
|
Sign up to set email alerts
|

Manufacturing Processes for Combined Forming of Multi-Material Structures Consisting of Sheet Metal and Local CFRP Reinforcements

Abstract: A new and promising approach to the reduction of greenhouse gas emissions is the use of improved lightweight constructions based on multi-material systems comprising sheet metal with local carbon fibre reinforced plastic (CFRP) reinforcements. The CFRP is used to reinforce highly stressed areas and can be aligned to specific load cases. The locally restricted application of CFRP means that the material costs can be effectively reduced by comparison to parts made entirely of CFRP on account of the expensive pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
4
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 2 publications
0
4
0
Order By: Relevance
“…Heggemann and Homberg [ 10 ] demonstrated that the shape and dimensional accuracy of deep drawn fiber metal laminates could be significantly improved by implementing pre-curing processes before the actual combined forming and curing process. Schmidt et al [ 11 ] optimized the combined forming of sheet metal and composite prepregs based on the detailed knowledge of the material behavior. The application of blank-holder force and blank-holder gap was found to have a positive effect on the formability of GLARE [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…Heggemann and Homberg [ 10 ] demonstrated that the shape and dimensional accuracy of deep drawn fiber metal laminates could be significantly improved by implementing pre-curing processes before the actual combined forming and curing process. Schmidt et al [ 11 ] optimized the combined forming of sheet metal and composite prepregs based on the detailed knowledge of the material behavior. The application of blank-holder force and blank-holder gap was found to have a positive effect on the formability of GLARE [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…Multi-material refers to a method for increasing strength and reducing weight by using various materials such as steel, aluminum alloy and carbon fiber reinforced plastic (CFRP) together [1][2][3][4]. In the multi-material, the dissimilar material joining technology is an indispensable core technology.…”
Section: Introductionmentioning
confidence: 99%
“…Novel one-step hybridization approaches combine the simultaneous formation of CFRP and metal layers and lead to reduction of used energy (in form of heating), process time, and cycle times. Therefore, efficient manufacturing objectives focus on combined formation of CFRP-reinforced metal structures. …”
Section: Introductionmentioning
confidence: 99%
“…Internal stress and brittleness create new problems in the manufacturing chain. Processing, like bending, folding, or combined forming, , is difficult, because of the composite’s low deformation performance and tendency for creasing and kinking. …”
Section: Introductionmentioning
confidence: 99%